2008
DOI: 10.1016/j.psychres.2007.07.010
|View full text |Cite
|
Sign up to set email alerts
|

Further development of YBOCS dimensions in the OCD Collaborative Genetics Study: Symptoms vs. categories

Abstract: Despite progress in identifying homogeneous subphenotypes of obsessive compulsive disorder (OCD) through factor analysis of the Yale-Brown Obsessive Compulsive Scale Symptom Checklist (YBOCS-SC), prior solutions have been limited by a reliance on presupposed symptom categories rather than discrete symptoms. Furthermore, there have been only limited attempts to evaluate the © 2007 Elsevier Ireland Ltd. All rights reserved. *Corresponding author: Anthony Pinto, Ph.D., Butler Hospital, 345 Blackstone Blvd., Provi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
115
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 144 publications
(123 citation statements)
references
References 44 publications
7
115
0
1
Order By: Relevance
“…Persons with GDs and OCD had significantly earlier ages at onset of OCD symptoms (median 6 years in persons with GD, median 8 without, Mann-Whitney P < 0.0005). GDs were not strongly or specifically related to particular OCD symptom dimensions derived from a factor analysis of Yale-Brown ObsessiveCompulsive Scale Symptom Checklist items [Pinto et al, 2008]. Using polychoric correlations, we found that the five OCD symptom dimensions (symmetry/ordering, taboo thoughts, hoarding, doubt/checking, and contamination/ cleaning) related more strongly to each other than to grooming disorders ( Table I).…”
Section: Figmentioning
confidence: 81%
“…Persons with GDs and OCD had significantly earlier ages at onset of OCD symptoms (median 6 years in persons with GD, median 8 without, Mann-Whitney P < 0.0005). GDs were not strongly or specifically related to particular OCD symptom dimensions derived from a factor analysis of Yale-Brown ObsessiveCompulsive Scale Symptom Checklist items [Pinto et al, 2008]. Using polychoric correlations, we found that the five OCD symptom dimensions (symmetry/ordering, taboo thoughts, hoarding, doubt/checking, and contamination/ cleaning) related more strongly to each other than to grooming disorders ( Table I).…”
Section: Figmentioning
confidence: 81%
“…Specifically, those receiving ketamine had lower mean estimated baseline OCD-VAS score at mid-infusion (by À 4.52 points, SE ¼ 1.23, po0.005), 230 min (by 3.84 points, SE ¼ 1.59, po0.05), and 7 days (by À 3.67 points, SE ¼ 1.36, po0.05) post infusion, each with large effect size (Cohen's d40.8), Abbreviations: A, Asian; AA, African American; C, Caucasian; EX/RP, cognitive behavior therapy with exposure and response prevention; F, female; H, Hispanic; HDRS, Hamilton Depression Rating Scale; M, male; MDD, major depressive disorder; OCD, obsessive-compulsive disorder; SAD, social anxiety disorder; SP, specific phobia; SRI, serotonin reuptake inhibitor; Y-BOCS, Yale-Brown Obsessive-Compulsive Scale. Symptom dimensions were based on a five-factor model (Pinto et al, 2008;Schooler et al, 2008) and listed in order of clinical severity for each subject: Cln (contamination/cleaning); Dbt (doubt/checking); Hrd (hoarding); Sym (symmetry/ordering); Tab (taboo thoughts (aggressive, sexual, and religious obsessions)). Y-BOCS was rated at baseline before infusion (pre) and 1-week post-infusion (post).…”
Section: First-phase Analysismentioning
confidence: 99%
“…OCD and depressive severity were assessed by trained clinician raters using the Yale-Brown Obsessive Compulsive Scale (Y-BOCS; Goodman et al, 1989a, b) and the 17-item Hamilton Depression Rating Scale (HAM-D; Hamilton, 1960). The Y-BOCS checklist provided scores for each OCD patient along five symptom dimensions (contamination and cleaning, taboo thoughts, doubt and checking, symmetry and ordering, and hoarding), using the approach recommended by Pinto et al (2007Pinto et al ( , 2008Pinto et al ( , 2009). …”
Section: Subjectsmentioning
confidence: 99%